New mutations in flagellar motors identified by whole genome sequencing in Chlamydomonas - Lin, Huawen (BioMed Central, 2013)
BACKGROUND: The building of a cilium or flagellum requires molecular motors and associated proteins that allow the relocation of proteins from the cell body to the distal end and the return of proteins to the cell body in a process termed intraflagellar transport (IFT). IFT trains are carried out by kinesin and back to the cell body by dynein. METHODS: We used whole genome sequencing to identify the causative mutations for two temperature-sensitive flagellar assembly mutants in Chlamydomonas and validated the changes using reversion analysis. We examined the effect of these mutations on the localization of IFT81, an IFT complex B protein, the cytoplasmic dynein heavy chain (DHC1b), and the dynein light intermediate chain (D1bLIC). RESULTS: The strains, fla18 and fla24, have mutations in kinesin-2 and cytoplasmic dynein, respectively. The fla18 mutation alters the same glutamic acid (E(24)G) mutated in the fla10-14 allele (E(24)K). The fla18 strain loses flagella at 32?C more rapidly than the E(24)K allele but less rapidly than the fla10-1 allele. The fla18 mutant loses its flagella by detachment rather than by shortening. The fla24 mutation falls in cytoplasmic dynein and changes a completely conserved amino acid (L(3243)P) in an alpha helix in the AAA5 domain. The fla24 mutant loses its flagella by shortening within 6 hours at 32?C. DHC1b protein is reduced by 18-fold and D1bLIC is reduced by 16-fold at 21?C compared to wild-type cells. We identified two pseudorevertants (L(3243)S and L(3243)R), which remain flagellated at 32?C. Although fla24 cells assemble full-length flagella at 21?C, IFT81 protein localization is dramatically altered. Instead of localizing at the basal body and along the flagella, IFT81 is concentrated at the proximal end of the flagella. The pseudorevertants show wild-type IFT81 localization at 21?C, but proximal end localization of IFT81 at 32?C. CONCLUSIONS: The change in the AAA5 domain of the cytoplasmic dynein in fla24 may block the recycling of IFT trains after retrograde transport. It is clear that different alleles in the flagellar motors reveal different functions and roles. Multiple alleles will be important for understanding structure-function relationships.